Outcomes of the Harada–Ito Procedure. Issue 3 (3rd July 2021) - Murray, Craig; Marsh, Ian; Newsham, David
ABSTRACT: Purpose: Fell's modification of the Harada–Ito (HI) procedure is often used to tackle subjective torsion usually following superior oblique palsy. There is limited published data on the longer-term outcomes and the effect on horizontal incomitance of the procedure. The purpose of this study is to report on the medium to long-term outcomes of the HI procedure. Materials and methods: A retrospective review of 20 patients who had all undergone a single surgeon modified HI procedure to correct subjective torsion was undertaken. Follow-up data were analyzed in relation to stability of torsion measurements, the effect on vertical incomitance of horizontal deviation and the final treatment outcome. Results: There was a significant reduction in median maximum torsion from preoperative to immediately post-op ( p < .01) and there remained a significant difference in maximum torsion from preoperative measurement at both the 3-month ( p = .02), and 12-twelve month ( p = .01) follow-up. HI had a significant effect on associated V-pattern esotropia ( p < .05). Conclusion: The HI procedure is effective in eliminating subjective torsion initially and reducing incomitant horizontal deviation; however, regression toward preoperative torsion measurement occurs after time.